Oxidative Addition Reactions of I2 with [HIr4(CO)10-n(PPh3 )n(m-PPh2)] (n = 1 and 2) and Crystal and Molecular Structure of [HIr4(m-I)2(CO)7 (PPh3)(m-PPh2)] - Braga Dario; Grepioni Fabrizia; Vargas Maria D.; Ziglio Claudio M. (Journal of the Brazilian Chemical Society, 2002)
The reactions of the cluster compounds [HIr4(CO)10-n(PPh3 )n(mu-PPh2)] [n = 0, (1); 1, (2) and 2, (3)] with I2 have been investigated. Compound 1 does not react, however, the presence of PPh3 in place of CO ligand(s) activates the cluster. Both compounds 2 and 3 react with I2 under mild conditions to give [HIr4(mu-I)2(CO)7(PPh3)(mu-PPh 2)] (4), as the result of oxidative addition of I2 and dissociation of two CO ligands, or one CO and one PPh3 ligands, respectively. The molecular structure of 4, determined by an X-ray diffraction study, exhibits a butterfly arrangement of iridium atoms with the wings spanned by a mu-PPh2 ligand, the hinge bridged by a mu-H ligand, two hinge to wing tip edges bridged by iodine atoms and all metal atoms bearing two CO ligands, with the exception of one of the hinge atoms that contains a CO and a PPh3 ligands. This cluster exhibits the shortest average Irfraction three-quartersIr bond length [2.698(2) Å] observed so far for a derivative of 1 and this is in accord with the relatively high average oxidation state of its metal atoms (+1) for a carbonyl cluster compound.